Abilities and Success - Boylan, David (Proceedings of the Amsterdam Colloquium, 2019)
Does success entail ability? Call the principle that it does Success: Success. S φ’s ⊨ S can φWhen we focus on successful action, Success is compelling: when someone succeeds in something, like sinking a putt or surfing a wave, one is forced to concede they were able to do that. This is what Success would lead us to expect. But when success is not yet assured, the lesson seems different. When said before the fact, the claim that I can surf that wave is strong — it says that surfing that wave is within my control. This intuition drives against Success. Just doing something does not demonstrate it is within my control: flukes do happen. So, if the control intuition is right, success should not demonstrate ability. First I try to make the above tension precise. I argue that the appeal of Success is connected to two plausible and related principles: that past success entails past ability, which I call Past Success; and that cannot seems to entail will not, which I call Can’t-entails-won’t. But, on the other, I show we can find counterexamples to Success in cases of inexact ability discussed by Kenny [1976]. To explain these data, I maintain we must connect the truth of ability claims to the facts about what our options settle and what they leave open, in the sense familiar from the literature on future contingents. I do this within a kind of conditional analysis of ability ascriptions. I first define an operator W with features attributed to ‘will’ in the literature on future contingents. In particular, Wφ is indeterminate in truth-value, when φ is unsettled. Building on previous joint work in Mandelkern et al. [2016], I state my conditional analysis in terms of W-conditionals: on my view, ⌜S can φ⌝ says, roughly, there’s some action available to S such that if S does it, then W(S φ’s) is true. By thus building a connection between unsettledness and indeterminacy into ability claims, my conditional account of abilities reconciles the motivations for Success with its counterexamples.